A Novel Bifunctional Fusion Protein, Vunakizumab-IL22, for Protection Against Pulmonary Immune Injury Caused by Influenza Virus - Han, Lei; Shi, Chenchen; Zeng, Xian; Cen, Lifeng; Mei, Xiaobin; Fan, Jiajun; Ju, Dianwen; Zhu, Haiyan (Frontiers in Immunology, 2021)
Influenza A virus infection is usually associated with acute lung injury, which is typically characterized by tracheal mucosal barrier damage and an interleukin 17A (IL-17A)-mediated inflammatory response in lung tissues. Although targeting IL-17A has been proven to be beneficial for attenuating inflammation around lung cells, it still has a limited effect on pulmonary tissue recovery after influenza A virus infection. In this research, interleukin 22 (IL-22), a cytokine involved in the repair of the pulmonary mucosal barrier, was fused to the C-terminus of the anti-IL-17A antibody vunakizumab to endow the antibody with a tissue recovery function. The vunakizumab-IL22 (vmab-IL-22) fusion protein exhibits favorable stability and retains the biological activities of both the anti-IL-17A antibody and IL-22 in vitro. Mice infected with lethal H1N1 influenza A virus and treated with vmab-mIL22 showed attenuation of lung index scores and edema when compared to those of mice treated with saline or vmab or mIL22 alone. Our results also illustrate that vmab-mIL22 triggers the upregulation of MUC2 and ZO1, as well as the modulation of cytokines such as IL-1β, HMGB1 and IL-10, indicating the recovery of pulmonary goblet cells and the suppression of excessive inflammation in mice after influenza A virus infection. Moreover, transcriptome profiling analysis suggest the downregulation of fibrosis-related genes and signaling pathways, including genes related to focal adhesion, the inflammatory response pathway, the TGF-β signaling pathway and lung fibrosis upon vmab-mIL22 treatment, which indicates that the probable mechanism of vmab-mIL22 in ameliorating H1N1 influenza A-induced lung injury. Our results reveal that the bifunctional fusion protein vmab-mIL22 can trigger potent therapeutic effects in H1N1-infected mice by enhancing lung tissue recovery and inhibiting pulmonary inflammation, which highlights a potential approach for treating influenza A virus infection by targeting IL-17A and IL-22 simultaneously.